Learning in High Stakes Ultimatum Games: An Experiment in the Slovak Republic - Slonim, Robert; Roth, Alvin E. (Econometrica, 1998)
In an ultimatum game experiment, financial incentives were varied by a factor of twenty-five. Consistent with prior results, changes in stakes had only a small effect on play for inexperienced players. However, rejections were less frequent the higher the stakes and proposals in the high stakes declined slowly as proposers gained experience. The lower rejection frequency when stakes were higher can be explained by the added power of multiple observations per subject in this experiment. A model of learning suggests that the lower rejection frequency is the reason proposers in higher stakes learn to make lower offers.